Introduction to applied pharmacoeconomics - Vogenberg, F. Randy (New York : McGraw-Hill, Medical Pub. Division, 2001)
In the brave new world of pharmaceutical care, pharmacists are being held accountable for measuring and documenting the quality and efficiency of services they provide. Given this, plus the changes in health delivery system wrought by managed care, economic issues are a prime area of concern. This title presents pharmaceutical economics in the context of how it can be applied in the marketplace setting. The book explores commonly used pharmacoeconomic evaluations, applying pharmacoeconomic evaluations into care paths and drug therapy algorithms, dealing with common barriers to pharmacoeconomic evaluations, and modelling versus patient-based evaluations.
Machine derived contents note: Chapter 1: US Health Care System and Pharmacoeconomics. -- Chapter 2: Traditional Paradigms in Pharmacoeconomics: Consideration for Cost-Effective Designs. -- Chapter 3: The Role and Use of Outcomes Assessments. -- Chapter 4: Principles of Drug Literature evaluation. -- Chapter 5: Use and Evaluation of Pharmacoeconomics from the Payers' Perspective. -- Chapter 6: Variable in Pharmacoeconomics. -- Chapter 7: Application of Pharmacoeconomics: Cost-Effective Analysis in Behavioral Health. -- Chapter 8: Application of Pharmacoeconomics and Decision Analysis in Gastrointestinal Disorders in the Context of Disease Management. -- Chapter 9: Application of Pharmacoeconomics in Cardiovascular Disease: Economic Evaluation of Lipid-Lowering Therapies. -- Chapter 10: Application of Pharmacoeconomics: Respiratory Diseases. -- Chapter 11: Guidelines and Information Requirements. -- Chapter 12: Pharmacoeconomic Applications. -- Chapter 13: Government Regulation of Health Care Economic Information.
Includes bibliographical references and index.
Keywords: CHEMOTHERAPY -- ECONOMIC ASPECTS; OUTCOME ASSESSMENT (MEDICAL CARE).; COST EFFECTIVENESS; PHARMACEUTICAL INDUSTRY; PHARMACY -- ECONOMIC ASPECTS